SARS-Cov-2 Systems Biology - José Díaz (Annals of Systems Biology - Peertechz Publications, 2020)
The aim of this mini review is to analysis the advances in the research of the SARS-CoV-2 molecular structure and pathogenesis from a systems biology approach. Introduction: Experimental analysis of the interaction of viral and host proteins, or interactome, by Gordon and collaborators has been a fundamental contribution to understand the form in which SARS-CoV-2 virus takes control of the host molecular network to produce new virions and propagate the infection. This result allows the construction of the viral network representation of the interactome and its statistical analysis. Formulation of network models of this interactome is a basic tool to identify drug targets capable of interrupt the viral replication cycle, and for the design of novel therapeutic agents. Discussion: SARS-CoV-2 is a free-scale hierarchical modular structure in which the open reading frame 8 protein, nucleocapside protein (N), and nonstructural protein 7 (Nsp7) are the central hubs. This kind of organization confers an extra level of complexity to this molecular network allowing it to resist the attack of drugs on single nodes. However, simultaneous suppression of these three hubs can effectively disrupt the network. Conclusions: Systems biology approach to the analysis of the SARS-CoV-2 interactome reveals the existence of six nodes that belong to high modularity classes (open reading frame 8 protein (orf8), Membrane protein (M), open reading frame 9b protein (orf9b), Nucleocapside protein (N), open reading frame 10 protein (orf10), Envelope protein (E), open reading frame 6 protein (orf6), open reading frame 7 protein (orf7) and Spike protein (S)) and control the flow of information during infection. These proteins are possible targets for new drugs, principally for antagonist of the three proteins orf8, M and Nsp7 that are the main bottlenecks throw which most of the information required for the production of new virus must flow. A therapeutic attack on these hubs can increase the probability to defeat viral infection as an alternative to a vaccine.